Insect parasitism - Hanson, Otto Albert (My University, 1905)
Introduction: "Parasitism in its broadest sense means degeneration." The first phase of parasitism appears when an insect loses the power to use some Particular organ, upon which its maintenance depends, and a gradual modification of this organ, with others, makes the parasite wholly dependent on its host for survival. Parasitism may be considered under two heads: periodical, and permanent parasitism. We have an example of periodical parasitism then the insect is a parasite for only a part of its life, and an example of permanent parasitism when the insect is a parasite during its entire life. We have an example of true parasitism when the parasite receives the benefit and the host the injury, if any. In nearly every case of insect parasitism the parasite is injurious to the host. Parasitism is a law of nature, and in order to preserve a balance among insects, nature has done so through the agency of parasitism. When there is an unusual number of insects present in a community, according to the law of nature, parasites will appear- in greater or less number, checking their increase, and in some cases nearly destroying them entirely. Parasites that belong to the Mallophaga, Pediculidae, and Sarcoptidae, which do not come strictly under the subject of insect parasitism, have obtained their parasitic habit through degeneration. The insect parasites, which nearly all come in the orders Hymenoptera and diptera, as a rule do practically all the injury to other insects in the larval stage. The adult parasite deposits its eggs in while cocoon of a host insect, and in performing this operation the insect within the cocoon usually killed. When the eggs hatch, the larvae feed upon the dead insect until they pupate, when they issue from the cocoon and in turn deposit eggs with their ovipositor in other cocoons.
Citation: Hanson, Otto Albert. Insect parasitism. Senior thesis, Kansas State Agricultural College, 1905.
Morse Department of Special Collections
Keywords: Hymenopterous Parasites; Pimpla Inquisitor; Pimpla Annulipes; Theses